Specialized Transduction Designed for Precise High-Throughput Unmarked Deletions in Mycobacterium tuberculosis - Paras Jain (American Society for Microbiology, 2014)
ABSTRACT Specialized transduction has proven to be useful for generating deletion mutants in most mycobacteria, including virulent Mycobacterium tuberculosis. We have improved this system by developing (i) a single-step strategy for the construction of allelic exchange substrates (AES), (ii) a temperature-sensitive shuttle phasmid with a greater cloning capacity than phAE87, and (iii) bacteriophage-mediated transient expression of site-specific recombinase to precisely excise antibiotic markers. The methods ameliorate rate-limiting steps in strain construction in these difficult-to-manipulate bacteria. The new methods for strain construction were demonstrated to generalize to all classes of genes and chromosomal loci by generating more than 100 targeted single- or multiple-deletion substitutions. These improved methods pave the way for the generation of a complete ordered library of M. tuberculosis null strains, where each strain is deleted for a single defined open reading frame in M. tuberculosis. IMPORTANCE This work reports major advances in the methods of genetics applicable to all mycobacteria, including but not limited to virulent M. tuberculosis, which would facilitate comparative genomics to identify drug targets, genetic validation of proposed pathways, and development of an effective vaccine. This study presents all the new methods developed and the improvements to existing methods in an integrated way. The work presented in this study could increase the pace of mycobacterial genetics significantly and will immediately be of wide use. These new methods are transformative and allow for the undertaking of construction of what has been one of the most fruitful resources in model systems: a comprehensive, ordered library set of the strains, each of which is deleted for a single defined open reading frame.